Subtitling Analysis Of Sentences In Son Of God Movie By Josephermlase - Siswati, Siti; , Dr. DwiHaryanti, M.Hum (2016)
The research aims at (1) classifying the unit shift of sentences of the subtitling in Son of God Movie and (2) describing the accuracy of the subtitling in Son of God Movie. This research paper belongs to descriptive qualitative research. The object of this study is a film entitled Son of god Movie. The data of this research are simple sentence, compound sentence, complex sentence and compound- complex sentence consisting subtitle in Son of God Movie. The data sources are a document of movie script entitled Son of God and informant . The method of collecting data that the reseacher uses are documentation and questionare. In the data validity, the reseacher uses source triangulation and method triangulation. The first result shows that there are three unit shifts of simple sentence, two unit shifts of compound sentence, and one unit shift of complex sentence. They are 4 data (0, 53%) of simple sentences that are translated to word. 2 data (0, 27%) of simple sentences are translated to phrase. 1 datum (0, 13%) of simple sentences is translated to complex sentence. 1 datum (0, 13%) of compound sentences is translated to simple sentence. 1 datum (0, 13%) of compound sentences is translated to complex sentence 8 data (1, 06%) of complex sentences are translated to simple sentence. There are 736 (97, 75%) of sentences that are translated to the same unit. The second result shows that there are three level of accuracy. There are 658 data(87, 39) belongs to accurate. 90 data (11, 95%) belongs to less accurate. 5 data (0, 66%) belongs to inaccurate.